The Influence of Ship To Ship (STS) Operational Efficiency and Weather Factors on the Smoothness of Cargo Distribution at PT. Ciomas Ariya Berkah - Hanik, Kumila; Setiawan, Endrik Nofri; Yulianto, Andri; Latuheru, Paulina M (IWTJ : International Water Transport Journal, 2025)
In this study, the researcher used a quantitative descriptive research method. This study aims to determine the effect of the variables studied, namely Ship to Ship (STS) Operational Efficiency and Weather Factors on the Smoothness of Cargo Distribution at PT. Ciomas Ariya Berkah. This research was conducted on a ship owned by the stevedoring company PT. Ciomas Ariya Berkah headquartered at Jl. Lingkar Selatan KM. 8.5 Link. Jerenong RT. 015 RW. 005 Kel. Lebak Denok Kec. Citangkil, Cilegon-Banten. While the effective research time took place from January to March 2025. The results of statistical testing with multiple linear regression equations obtained that partially the Ship to Ship (STS) operational efficiency variable on the smoothness of cargo distribution at PT. Ciomas Ariya Berkah. The results of statistical testing with multiple linear regression equations obtained that partially the weather factor variable on the smoothness of cargo distribution at PT. Ciomas Ariya Berkah. The results of statistical testing with multiple linear regression equations obtained that partially the weather factor variable on the smoothness of cargo distribution at PT. Ciomas Ariya Berkah. Where indicated by a significance value of 0.046.